Development Efforts of Sopi Production and Its Derivative Products to Support Household Income in Hatusua Village, Kairatu Subdistrict, West Seram Regency - Tupasouw, Thabita; Riry, Johan; Riry, Roberth Berthy (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2025)
Sopi production in Hatusua Village is a traditional economic activity that contributes significantly to household income. This study aims to evaluate the contribution of sopi enterprises to family income and assess their viability using a descriptive quantitative approach. The sample consisted of ten sopi farmers selected through total sampling, with data collected via observation, interviews, and documentation. The analysis employed the Benefit-Cost Ratio (B/C Ratio) method. The findings revealed that the average weekly income of farmers reached IDR 1,200,000, yet all respondents recorded B/C values below 1, indicating that the enterprise is not financially viable. The main contributing factors include high fuel costs, reliance on manual tools, and limited market access. While sopi holds strong economic and cultural potential, strategic improvements through training, appropriate technology adoption, product legalization.